The Effectiveness of Farmers’ Group Functions in Creating Self- sustain of Beef Cattle Farming Activities - Haryadi, F. Trisakti (2014)
The objectives of the study were (1) to evaluate the functions of farmers group in creating self -sustain of beef cattle farming activities, and (2) to analyze the influence of personal farmers’ characteri stics on the effectiveness of farmers’ group functions . All of the member of Ngudi Barokah farmers’ group were selected as the respondents. Data were collected by interviewing the farmers directly using questionnaire. Descriptive and m ultiple linear regres sion analys es were used as a tool of data analyses. The results showed that the farmers’ group functions as a place of learning (85.70%), a production unit (76.20%%), and a mean of cooperation (76.20%) were in the high categories, while the function as a business unit (57.10% ) was still in low category. The number of beef cattle raised influenced positively the farmers’ group functions as a mean of cooperation (P<0.10) and a business unit (P<0.05). The effectiveness of the farmers’ group function as a plac e of learning was influence d positively by the economic motive (P<0.10) and the farmer experience in beef cattle farming (P<0.10). Economic motive also influenced positively (P<0.10) the farmers’ group function as a production unit. The conclusion was that the beef cattle farmers could be facilitated in a good situation for their learning, production, and cooperation processes in the farmers group, but not good yet for business. The number of beef cattle raised , economic motive, and the farmer experience in beef cattle farming, were important variables to improve the effectiveness of farmers group functions in creating self -sustain of beef cattle farming activities.